2018
DOI: 10.1097/cmr.0000000000000456
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trends in the diagnosis of melanoma in a Southern European population: analysis of a large database from a tertiary referral center

Abstract: The aim of this study was to present the epidemiological, clinicopathological, and treatment characteristics of patients diagnosed and treated in a tertiary referral center and to analyze independent factors associated with these characteristics. In this cohort study, epidemiological, clinicopathological, and treatment characteristics of 1461 consecutive melanoma patients diagnosed and treated in a tertiary referral center in 1987-2015 were prospectively collected in a registry. All patients underwent resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In this study, patient characteristics were generally consistent with those who received nivolumab monotherapy in the CheckMate 067 study . However, the percentage of tumor types reported in Japan for acral lentiginous (46%), superficial spreading (23%) and mucosal (10%) is different to what has been reported in other countries (5%, 54% and .4% respectively) . It has been reported that acral lentiginous (50%‐58%) and mucosal (15%) melanoma are common subtypes in Asian countries.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, patient characteristics were generally consistent with those who received nivolumab monotherapy in the CheckMate 067 study . However, the percentage of tumor types reported in Japan for acral lentiginous (46%), superficial spreading (23%) and mucosal (10%) is different to what has been reported in other countries (5%, 54% and .4% respectively) . It has been reported that acral lentiginous (50%‐58%) and mucosal (15%) melanoma are common subtypes in Asian countries.…”
Section: Discussionsupporting
confidence: 76%
“…(23%) and mucosal (10%) is different to what has been reported in other countries (5%, 54% and .4% respectively). 12 It has been reported that acral lentiginous (50%-58%) 13 and mucosal (15%) 14 melanoma are common subtypes in Asian countries. Thus, the percentage of tumors that are acral lentiginous or mucosal is higher in East Asian countries, including Japan, than in other countries.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…Acral lentiginous melanoma predominates in Japan (~40%), whereas the superficial spreading type predominates in other countries. 2 The proportions of acral lentiginous and mucosal melanoma types in Japan are higher than those reported in other countries 2,[11][12][13][14][15] and, as these types are known to harbor tumor mutations far less frequently than the superficial spreading type, 15 this may affect the effectiveness of nivolumab. Due to these differences, data confirming the long-term efficacy of nivolumab in Japanese melanoma patients are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the Caucasians melanoma patients have aggregative and progressive disease state, leading major cancer-related morbidity and mortality of skin disorder [3]. Ultraviolet (UV) radiation, race, lifestyle, and genetic differences are the most important reasons for the increase of melanoma related-mortality [8][9][10][11][12]. Early-stage detection and prevention of melanoma can reduce the mortality of MM and present the best survival [12,13].…”
Section: Introductionmentioning
confidence: 99%